Preservation of Steamed Fish (Rastrelliger Sp) With Combine Method Using Sodium Acetate, Lactic Acid Bacteria Culture and Vacuum Packaging - Betty Sri Laksmi Jenie; . Nuratifa; . Suliantari (Jurnal Teknologi dan Industri Pangan, 2001)
This study was carried out to improve the safety and shelf life of cooked kembung fish (Rastrelliger sp), a traditional food called pindang fish. Fresh eviscerated fish was fisrt soaked in 2% NaCl solution for 15 minutes, drained, washed with tap water and drained again. Sodium chloride at 12% concentration (w/w) was distributed on the whole surface of the fish. Fish was then laid on a wooden basket inside a clay pot, steamed for 30 minutes, and then cooled. Combine method applied to the steamed fish (pindang) was soaking in a mixed culture of Lactobacillus plantarum kik and Lactococcus lactis subsp. cremoris in the ratio of 2 : 1 (v/v) containing 4% Na-acetate for 2 hrs and after draining, the product was vacuum packed. The result showed that the combine method using mixed culture of lactic acid bacteria containing 4% Na-acetate could reduce the growth of Staphylococcus aureus by 3-6 log units, decrease the TMA (Trimethylamine) content and maintain the organoleptic properties (texture, appearance and odor) of pindang fish during 6 days storage at room temperature. Control treatment without 4% Na-acetate could only keep the pindang fish for 4 days. Vacuum and nonvacuum packaging did not show any significant difference.